Pengaruh Kompensasi dan Motivasi Kerja terhadap Kinerja Karyawan pada PT. Bambu Cemerlang Express Hub Aje Rajeg di Kabupaten Tangerang - Dewi Nari Ratih Permada; Didi Sunardi; Haris Baihaqi; Priehadi Dhasa Eka (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid development of the logistics industry has encouraged companies to improve employee performance in order to maintain operational effectiveness and customer satisfaction. Employee performance is influenced by various factors, including compensation and work motivation. At PT. Bambu Cemerlang Express Hub Aje Rajeg, several problems related to employee performance were identified, such as low work quality, lack of responsibility, and insufficient employee motivation due to limited compensation and employee welfare support. Therefore, this study aimed to analyze the effect of compensation and work motivation on employee performance at PT. Bambu Cemerlang Express Hub Aje Rajeg, Tangerang Regency. This study employed a quantitative research approach using a survey method. The respondents consisted of 83 employees selected through a census sampling technique. Research data were collected through the distribution of Likert-scale questionnaires. The study was conducted at PT. Bambu Cemerlang Express Hub Aje Rajeg, located at Jl. Raya Rajeg, RT.04 RW.04, Daon, Rajeg District, Tangerang Regency, Banten 15540. The data were processed using SPSS version 27 and analyzed through multiple linear regression analysis. The results revealed that compensation and work motivation partially and simultaneously had a positive and significant effect on employee performance. Work motivation showed the strongest influence on employee performance. These findings indicate that improving compensation policies and employee motivation can enhance employee performance and organizational productivity.